OP18 Trends and inequalities in suicide, drug and alcohol related mortality among young men aged 15–44 in Scotland, 1980–2013: analysis of routine data. (13th September 2016) - Dundas, R; Curnock, E; Allik, M; Brown, D; Leyland, AH
Abstract : Background: Health inequalities have persisted or increased across Western Europe. In Scotland, population health is poorer than in comparable countries and health inequalities are alarmingly high, particularly among young adults. Addressing health inequalities is a priority for UK and international governments. The aim was to determine the trends and socioeconomic inequalities in cause specific mortality among Scottish men aged 15–44 from 1980–2013. Methods: Routine death data were linked to mid-year population estimates for men aged 15–44 in Scotland for 1980–2013. Directly standardised mortality rates were calculated for all-cause and suicide, drug and alcohol related harm. Trends in inequalities were examined for 2002–2013 using deprivation measured by the income domain of the Scottish Index of Multiple Deprivation. Inequalities were measured using the slope index of inequality (SII) and the relative index of inequality (RII). Results: Overall there were 52, 551 deaths in men aged 15–44 from 1980–2013. All-cause mortality decreased from 159 per 100, 000 in 1980 to 130 per 100, 000 in 2013. Mortality rates from suicide increased from 22 to 41 per 100, 000 from 1980 to 2000, then decreased to 29 in 2013. Mortality from drug related deaths increased from 1 to 25 per 100, 000 from 1980–2013; and alcohol related deaths increased from 5 to 12 per 100, 000. In 1980 18% of deaths were due to suicide, drug and alcohol related mortality; by 2013 the contribution from these three causes increased to 51%. Inequalities in mortality in 2002–04 were high, with SII for suicide 59.3 (95% CI = 52–66); drug 64.0 (59–69) and alcohol 53.4 (49–57). For 2011–13 the SII for suicide remained the same at 55.4 (95% CI = 49–62); drug increased to 63.8 (59–69) and alcohol reduced to 34.4 (31–38). During both time periods 60% of the SII for total mortality was due to these 3 causes. In 2011–13 ischaemic heart disease (the next highest) contributed 7.3%. The RII remained constant for suicide 2002–04: 0.37 (95% CI = 0.33–0.41), 2011–13: 0.40 (0.35–0.45); increased for drugs 2002–04: 0.40 (95% CI = 0.37–0.43), 2011–13: 0.46 (0.42–0.50); and decreased for alcohol 2002–04: 0.33 (0.31–0.36), 2011–13: 0.25 (0.22–0.27). Conclusion: Although deaths in men aged 15–44 are relatively uncommon, the use of population data enabled detailed examination of the causes of death. While there has been a reduction in mortality the underlying causes have changed and in the last decade inequalities in mortality remain high. Efforts to reduce suicide, drug and alcohol related mortality in young men living in deprived areas should be a priority for policy.